2001
DOI: 10.1016/s0168-9002(01)01561-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the TJNAF FEL with tapered and inversely tapered undulators

Abstract: Experiments using the TJNAF FEL have explored the operation with both tapered and inversely tapered undulators. We present here numerical simulations using the TJNAF experimental parameters, including the effects of taper. Singlemode simulations show the effect of taper on gain. Multimode simulations describe the evolution of short optical pulses in the far infrared, and show how taper affects single-pass gain and steady-state power as a function of desynchronism. A short optical pulse presents an ever-changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…For linear taper ðD ¼ 0Þ; we considered different values of d ¼ 7p; 72p; 74p corresponding to a change DK=K ¼ 70:9%; 71:9%; 73:8%; respectively. We found that negative taper, d ¼ Àp; À 2p gave the highest efficiency ZE0:9% at desynchronism d ¼ 0:04: This is similar to our simulations of the TJNAF 10 kW FEL [8]. For these cases, the full-width induced energy spread was Dg=g ¼ 3%; which is below the limit for safe recirculation.…”
Section: Steady State Powersupporting
confidence: 87%
“…For linear taper ðD ¼ 0Þ; we considered different values of d ¼ 7p; 72p; 74p corresponding to a change DK=K ¼ 70:9%; 71:9%; 73:8%; respectively. We found that negative taper, d ¼ Àp; À 2p gave the highest efficiency ZE0:9% at desynchronism d ¼ 0:04: This is similar to our simulations of the TJNAF 10 kW FEL [8]. For these cases, the full-width induced energy spread was Dg=g ¼ 3%; which is below the limit for safe recirculation.…”
Section: Steady State Powersupporting
confidence: 87%